The Impact of Affirmative Action on Skills Retention within the Banking Sector in South Africa - Maharaj, Anisa (My University, 2012)
Affirmative Action remains one of the most highly sensitive and debated subjects in South Africa. It is, nevertheless, important that legislation be fully researched and constructively debated to bring about change to the lives of previously disadvantaged population groups. The present study focused on the impact of Affirmative Action on skills retention within the Banking Sector. The goal was to establish how skilled employees within the Banking Sector experienced the impact of Affirmative Action. Emphasis was placed on how employees define Affirmative Action; whether or not they feel that others question their abilities because of Affirmative Action; and the extent to which Affirmative Action policies affect their job satisfaction. The research sought to establish if Affirmative Action is the reason why skilled employees are job hopping and or emigrating. A quantified research approach was used to study the views of 100 employees from the Banking Sector. Results of the study revealed that respondents viewed Affirmative Action as a positive factor to redress the imbalances of the past. The respondents were, however, of the opinion that Affirmative Action is a form of reverse discrimination. These results concur with those from previous research (Sowell 2004; Zelnick 2006). Respondents did not agree that Affirmative Action drives a wedge between selfesteem and success, finding which is contrary to previous research (Gillis, Gomes and Valliere 2001; Koekemoer 1998) that propound a high stress level and demotivation amongst those who are supposed to benefit from Affirmative Action. The current findings are congruent with Mikkelsen, Ogaard and Lovrichn (2000) where the assertion is that job stress caused by lack of training and development impacts turnover. The findings are also congruent with Johnson’s (2009) and BANKSETA’S (2008) assertion that the shortage of skills within the Banking Sector could be attributed to the policies of Affirmative Action
MBA thesis - WBS
Keywords: Skills retention; Affirmative action; Banks and banking